Learning Loss in ELT: Impact of Google Classroom for the Secondary School Students During Pandemic - Teguh Budiharso; Bulent Tarman; Imroatus Solikhah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This research explores the impact of implementing google classroom on online learning for secondary school students in learning English during the pandemic outbreak. This research used cyber ethnography and content analysis. Three schools, 12 English teachers and 15 students were involved in this study. Checklist and interview were used to collect data. Cyber ethnography analysis was used for data analysis. Results show that google classroom activities are restricted to apply g-meet as a consequence of limited infrastructure and internet access. Google classroom practices are perceived unsatisfied by teacher and students, making the teaching quality is low. Barriers in the application of google classroom are indicated by hardware barriers, software barriers, school barriers, electronic and IT barriers. The learning loss occurs in four different concerns: seasonal breaks, absence from school, covid-19 outbreak, low quality of teaching, and school service. This study has its novelty because it involves learning loss theory and implements cyber ethnography methods.